Meru - Chin, Jimmy; Vasarhelyi, Elizabeth Chai; Anker, Conrad; Ozturk, Renan (Chicago, IL : Music Box Films, 2015)
Three renowned climbers navigate nature's harshest elements and their own inner demons to ascend Mount Meru, the most technically complicated and dangerous peak in the Himalayas.
Originally released as a motion picture in 2015.
Dolby digital 5.1, anamorphic wide screen 1.78:1.
Features: additional footage.
Featuring Conrad Anker, Jimmy Chin, Renan Ozturk.
MPAA rating: R.
Keywords: Mountaineering expeditions -- Himalaya Mountains; Mountaineering -- Psychological aspects; Documentary films; Nonfiction films; Feature films